Canalis sinuosus mimicking root resorption lesion - Jaydeep Shashikumar Talim; Daniel Schechter; Rafael Roges; Ilan Rotstein (Wolters Kluwer Medknow Publications, 2018)
Anatomical variations in the premaxillary region, especially those involving neurovascular structures, can present a diagnostic challenge to a clinician. Correct diagnosis is crucial for treatment decision-making and prognosis assessment of nonsurgical and surgical procedures. Canalis sinuosus (CS) is an anatomical variation of the anterior superior alveolar nerve canal. Its diagnosis may sometimes be confusing, resulting in an inadequate treatment plan. Described is a case of a CS mimicking an external root resorption lesion. Cone beam computed tomography (CBCT) assisted in confirming the final diagnosis.